(untitled) (Ozone Therapy Global Journal, 2014)
When we look back we can measure with clarity how much we have advanced in the normative, associative, and training levels, and in common protocols for worldwide application of the ozone therapy. Regularization of ozone therapy The panorama that appeared before 2005 in relation to the practice of ozone therapy was bleak, there was literally nothing. The ozonetherapists were afraid, working practically in the dark, and adopting a low profile, to avoid arousing bad ideas by the health administrations. Research was conducted but for the authorities was not enough to demonstrate the safety and efficacy of the therapy.